Streptomyces Bacteria as Potential Probiotics in Aquaculture - Tan, Loh Teng-Hern; Chan, Kok-Gan; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Microbiology, 2016)
In response to the increased seafood demand from the ever-going human population, aquaculture has become the fastest growing animal food-producing sector. However, the indiscriminate use of antibiotics as a biological control agents for fish pathogens has led to the emergence of antibiotic resistance bacteria. Probiotics are defined as living microbial supplement that exert beneficial effects on hosts as well as improvement of environmental parameters. Probiotics have been proven to be effective in improving the growth, survival and health status of the aquatic livestock. This review aims to highlight the genus Streptomyces can be a good candidate for probiotics in aquaculture. Studies showed that the feed supplemented with Streptomyces could protect fish and shrimp from pathogens as well as increase the growth of the aquatic organisms. Furthermore, the limitations of Streptomyces as probiotics in aquaculture is also highlighted and solutions are discussed to these limitations.